2014
DOI: 10.1590/s2179-975x2014000400004
|View full text |Cite
|
Sign up to set email alerts
|

Diel dynamic of phytoplankton functional groups in a tropical water supply, Extremoz Lake, northeastern Brazil

Abstract: Aim: This study analyzed -the diel and vertical dynamics of phytoplankton functional groups in a natural tropical lake (Extremoz Lake, northeast Brazil), to investigate and understand the driver factors of the community during a severe drought period. Methods: Sampling of the abiotic variables and phytoplankton was performed at intervals of 6 hours over 24 hours in vertical profiles, in dry and rainy seasons (according to the historical average). The phytoplankton species were grouped according to the function… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
5
0
1

Year Published

2017
2017
2025
2025

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 25 publications
2
5
0
1
Order By: Relevance
“…In the same way, another study performed in a tropical water supply reservoir (Extremoz Lake, NE Brazil) also showed the dominance of Pl. limnetica under low values of phosphate-P (Pinto and Becker, 2014), in accordance with our results.…”
Section: Discussionsupporting
confidence: 93%
“…In the same way, another study performed in a tropical water supply reservoir (Extremoz Lake, NE Brazil) also showed the dominance of Pl. limnetica under low values of phosphate-P (Pinto and Becker, 2014), in accordance with our results.…”
Section: Discussionsupporting
confidence: 93%
“…The biomass of Planktolyngbya, a shade-adapted filamentous cyanobacterium (Fabbro & Duivenvoorden, 2000), was related to higher concentrations of suspended solids (VSS and TSS) and shallower depth, dominating year-round in the meso-eutrophic Tabatinga lake. In agreement with previous reports, Planktolyngbya has been associated with turbid environments, with mixed layers and relatively lower values of phosphate in Brazilian semiarid lakes (Pinto and Becker 2015;Barroso et al 2018). Meanwhile, Aphanocapsa, a coccoid cyanobacterium typically found in eutrophic environments (Padisák et al, 2009), was detected under mesotrophic conditions and associated to lower suspended solids and deeper water depth (Zmax).…”
Section: Discussionsupporting
confidence: 91%
“…It has a wet season that extends from February to July, with average precipitation of 184 mm per month, and a dry season from August to January, with average precipitation of 43 mm per month (INMET, 2020). Its maximum storage capacity is 11 million m 3 , it has a surface area of 3.59 km 2 (Rio Grande do Norte, 2015), and average depth of 4 m (Pinto & Becker, 2014). The lake's main use is water supply, as it provides water for 60%-80% of the population of the north region of Natal, Brazil (Araújo et al, 2000), therefore the quality of its water is of great importance.…”
Section: Study Areamentioning
confidence: 99%